Regulation of neural stem cell proliferation and survival by protein arginine methyltransferase 1 - Hashimoto, Misuzu; Takeichi, Kaho; Murata, Kazuya; Kozakai, Aoi; Yagi, Atsushi; Ishikawa, Kohei; Suzuki-Nakagawa, Chiharu; Kasuya, Yoshitoshi; Fukamizu, Akiyoshi; Nakagawa, Tsutomu (Frontiers in Neuroscience, 2022)
Protein arginine methyltransferase 1 (PRMT1), a major type I arginine methyltransferase in mammals, methylates histone and non-histone proteins to regulate various cellular functions such as transcription, DNA damage response, and signal transduction. PRMT1 is highly expressed in neural stem cells (NSCs) and embryonic brains, suggesting that PRMT1 is essential for early brain development. Although our previous reports have shown that PRMT1 positively regulates oligodendrocyte development, it has not been studied whether PRMT1 regulates NSC proliferation and its survival during development. To examine the role of PRMT1 in NSC activity, we cultured NSCs prepared from embryonic mouse forebrains deficient in PRMT1 specific for NSCs and performed neurosphere assays. We found that the primary neurospheres of PRMT1-deficient NSCs were small and the number of spheres was decreased, compared to those of control NSCs. Primary neurospheres deficient in PRMT1 expressed an increased level of cleaved caspase-3, suggesting that PRMT1 deficiency induced apoptosis. Furthermore, p53 protein was significantly accumulated in PRMT1-deficient NSCs. In parallel, p53-responsive pro-apoptotic genes including Pmaip1 and Perp were upregulated in PRMT1-deficient NSCs. p53-target p21 mRNA and its protein levels were shown to be upregulated in PRMT1-deficient NSCs. Moreover, the 5-bromo-2'-deoxyuridine (BrdU) incorporation assay showed that the loss of PRMT1 led to cell cycle defects in the embryonic NSCs. In contrast to the above in vitro observations, NSCs normally proliferated and survived in the fetal brains of NSC-specific PRMT1-deficient mice. We also found that Lama1, which encodes the laminin subunit α1, was significantly upregulated in the embryonic cortices of PRMT1-deficient mice. These data implicate that extracellular factors provided by neighboring cells in the microenvironment gave a trophic support to NSCs in the PRMT1-deficient brain and recovered NSC activity to maintain brain homeostasis. Our study implies that PRMT1 plays a cell-autonomous role in the survival and proliferation of embryonic NSCs.